Highly Diastereoselective Synthesis of Tetrahydroquinoline Derivatives via [4 + 2] Annulation of Ortho-Tosylaminophenyl-Substituted Para-Quinone Methides and Cyanoalkenes - Dong, Taiwei; Wei, Peifeng; Li, Min; Gao, Feng; Qin, Yuan (Frontiers in Chemistry, 2021)
As a privileged structural motif, tetrahydroquinoline skeletons widely exist in biologically active natural products and pharmaceuticals. In this protocol, a highly diastereoselective [4 + 2] annulation of ortho-tosylaminophenyl-substituted p-QMs and cyanoalkenes to construct tetrahydroquinoline derivatives has been successfully achieved. This strategy proceeds efficiently under mild condition, offering straightforward route to a variety of 4-aryl-substituted tetrahydroquinolines with high yields, excellent diastereoselectivities, broad functional group tolerance as well as gram-scale capacity. Moreover, a one-pot reaction sequence utilizing in situ generated p-QMs under the similar condition to build tetrahydroquinoline framework is smoothly conducted with good reaction performance as well as step and atom economy.